First-order contests for second-order parties? Differentiated candidate nomination strategies in European Parliament elections. Issue 7 (9th November 2016) - Daniel, William T.
Abstract: This article examines an alternative logic for candidate renomination to the European Parliament (EP), based upon the size and ideological nature of a Member of the European Parliament's (MEP's) home party, as well as timing of EP elections. I derive expectations from the second-order election hypothesis to show that parties from outside of the national mainstream should expect to benefit disproportionately from EP elections and therefore renominate experienced incumbents at higher rates. Using original data on the career behaviour of MEPs during the 2009 and 2014 elections, I find that such parties are more likely to treat EP contests as 'first order' in their importance, particularly when European elections are held during the midterm period of the national election cycle. My findings have new implications for the differentiated volatility of the EP, specifically, as well as for internal party dynamics in multi-level systems, more generally.